Muqarnas. - Leal, K. (Muqarnas, 2010)
Muqarnas: An Annual on the Visual Cultures of the Islamic World is sponsored by the Aga Khan Program for Islamic Architecture at Harvard University and the Massachusetts Institute of Technology, Cambridge, Massachusetts. The articles in Muqarnas 27 address topics such as spolia in medieval Islamic architecture, Islamic coinage in the seventh century, the architecture of the Alhambra from an environmental perspective, and Ottoman-Mamluk gift exchange in the fifteenth century. The volume also features a new section, entitled "Notes and Sources", with pieces highlighting primary sources such as Akbar's Kathāsaritsāgara . Contributors include Ebba Koch, Elizabeth Lambourn, Elias Muhanna, Rina Avner, Kathryn Moore, Alicia Walker, Todd Willmert, Julia Gonnella, Zeynep Ertuğ, Jere Bacharach, Persis Berlekamp, Heike Franke, Vincenza Garofalo, and Fabrizio Agnello.